Monastic Names in The Diptych of Dečani Monastery (XVI ‒ XX) - Rakić, Jugoslava G (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
In this paper we dealt with monastic names in The Diptych of Dečani Monastery, which records names in the period of time from the end of the 16th to the beginning of the 20th century. We excerpted the names from the sections that are provided for entering the names of monks and nuns, as well as from other sections in which the names of monks are written. All recorded monastic names are analyzed from the etymological and semantic aspect and from the aspect of their word formation, and next to each name in brackets we gave the number of how frequent it was among monks and nuns.The recorded male monastic names mostly belong to the group of calendar ones that appear very rarely, or do not appear among the people at all. Monastic female names are mostly names that are quite common among the people.
Keywords: The Diptych of Dečani Monastery; anthroponymy; names of monks